Rationality in risk-sensitive foraging choices by starlings - Schuck-Paim, C; Kacelnik, A (2002)
Normative models of choice usually predict preferences between alternatives by computing their value according to some criterion, then identifying the alternative with greatest value. An important consequence of this procedure is captured in the economic concept of rationality, defined through a number of principles that are necessary for the existence of an ordinal scale of value upon which organisms base their choices. Violations of these principles, such as some recently reported breaches of transitivity and regularity in birds and honeybees, have strong implications for the understanding of decision mechanisms in humans and nonhumans alike. We investigated rationality in risky choice using European starlings, Sturnus vulgaris. Birds had to choose between two or three food sources, each associated with a different variance in delay to reward. In three experiments, starlings were strongly risk prone, showing regular and consistent preferences in binary and trinary choices. Preferences also satisfied weak and strong stochastic transitivity. Our results extend the generality of previous research in risk-sensitive foraging to situations where more than two alternatives are present and suggest that violations of rationality in risk-sensitive choices may be expressed only under restricted sets of conditions. © 2002 The Association for the Study of Animal Behaviour. Published by Elsevier Science Ltd. All rights reserved.